How much of the forest sink is passive? Case of the United States - Eric C. Davis; Brent Sohngen; David J. Lewis (Proceedings of the National Academy of Sciences, 2026)
Over time, carbon sequestered in temperate forests has increased, but the relative effects of passive and active drivers remain unclear. This study uses plot-level data to disentangle the contributions of six drivers (temperature, precipitation, CO 2 , management, age composition, and area) to these increases in 14 forest groups of the conterminous United States. From 2005 to 2022, the passive drivers (CO 2 , temperature, and precipitation) increased live tree carbon (C) by 66 teragrams (Tg) C y −1 with CO 2 fertilization contributing most of the change. Among the anthropogenic drivers, declining forest area reduced live tree C by 31 Tg C y −1 while tree planting increased it by 23 Tg C y −1 . Changes in age composition, driven by both passive traits and anthropogenic choices, increased live tree C by 89 Tg C y −1 . By quantifying the share of removals attributable to passive uptake, this approach enables nations with national forest inventories to better utilize their forests to meet net-zero requirements.